Pemanfaatan Panas Buang Air Conditioner (AC) pada Lemari Pengering Benih Padi: Bachtera Indarto, Santi Puspitasari, Hasto Sunarno - Bachtera Indarto Bachtera Indarto; Santi Puspitasari Santi Puspitasari; Hasto Sunarno Hasto Sunarno (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
Research on the utilization of heat exhaust from air conditioner (AC) for paddy dryer cup board, has been successfully done. The objective of this research is to get the design of rice dryer cabinets by utilizing the exhaust heat from the air conditioner condenser and adjust the temperature and humidity of the air in the drying cabinet in accordance with the provision in drying process of riceseed. Dryer cabinet made of the type of traydryer, has 4 shelves and made of wood plywood plated aluminum foil dimension 50 cm x 50 cm x 60 cm with a capacityof 2 kg. The temperature and humidity settings of the drying cabinet are designed using SHT 11. This system produces riceseeds with moisture content of 11% after 10 hours of drying process. The temperature setting using exhaust fan works well during the drying process which is set at 30-43ºC, while the air humidity setting using blower can be maintained with valuea bove 42.55%.